Le fratture della mano in età pediatrica - Senes, F.M.; Arrigoni, C. (Lo Scalpello - Journal, 2018)
PAEDIATRICS HAND FRACTURESPhalangeal fractures are the most common hand fractures in children and the distal phalanx is the most injured.Minor fingertip injuries are very common; sometimes simple wound care might be enough but, in cases of larger skinloss, local or regional flaps could be required. Carpal fractures are rare, almost always observed in adolescents ratherthan in children, whereas metacarpal fractures are most commonly metaphyseal compression fractures orSalter–Harris type II physeal fractures.